Kompas Magnetik Digital dengan Keluaran Suara Berbasis Mikrokontroler AT89S51 - Rusgianto, Rusgianto; Misto, Misto (Jurnal Fisika FLUX, 2011)
An electronic compass system with sound output have been done. Thesystem was employed HM55B Compass Module Sensor, Microcontroller AT89S51,Operational Amplifier, and IC Voice ISD 2590.The operation of the system wascontroller by the microcontroller. The signal from the compass sensor is feed toATmega8535 microcontroller. On the otherhand, in twelve memory of voicedeviceISD2590 is recorded some word sound signal from the north to the north west.For reproducing the sound signal the data from microcontroller will switch on thememory according to itâs compass toward. The sound electronic signal is linked to thespeaker to produce sound. It was concluded that the system work well since the allparameter were displayed on the monitor simultaneously.